Pharmacognostical and phytochemical evaluation of Cinnamomum wightii Meissn. flowers - Laloo D.; Sahu A.N.; Hemalatha S.; Dubey S.D. (My University, 2025)
Cinnamomum wightii Meissn. (Family- Lauraceae) is a tree mainly found in the Western Ghats and Shola forest of the South India. Pharmacognostical and phytochemical evaluation of crude drug has been done as per WHO guidelines and IHP 2002. The crude flower buds are globoid to round in shape, dark brown with 1-2 cm long pedicel. Transverse section through petals showed both the outer and inner epidermis with numerous stone cells and secretory glands scattered in the cortex. The quantitative values found are: foreign organic matter (0.71%), loss on drying (11.88%), total ash (6.41%), acid insoluble ash (2.07%), water soluble ash (0.38%), alcohol soluble extractive (28.63%) and water soluble extractive (7.23%), foaming index (200), swelling index (0.85 ml), volatile oil content (0.20%) and pesticide residue content. The powdered crude flower buds have shown the presence of stone cells, vessel element, covering trichomes, spiral xylem vessel and fragments of anthers filamentous cell layer. Phytochemical screening of methanolic extract showed the presence of alkaloids, glycosides, flavonoids, saponins, coumarins, reducing sugars, phenolics, tannins, sterols and mucilage. Quantitative estimation of the methanolic extracts of various phytoconstituents, viz. total tannins (156.5 mg/g), total phenolics (146.40 mg/g), total flavonoids (30 mg/g) and total flavonols (3.6 mg/g) content has been estimated spectrophotometrically. These findings may serve as diagnostic tools for identification of the crude drug.